El pensamiento político de Clorinda Matto de Turner 1 - Ortiz Fernandez, Carolina (2007)
Which were the problems of Peru by the end of the 19th. century? How to solve them? Which were the ideas of country and nation? How to confront the inequality and the racial, genre and class domination and discrimination to have an affect overcoat on women and Indians? These are some of the questions that I attempt to respond by exploring not well known texts of Clorinda Matto de Turner, I talk about her journalistic articles, her traditions and legends, her reflections on various historical and social events in Peru and Latin America, without leaving aside her well-known novels.